2015
DOI: 10.1016/j.schres.2015.01.019
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal white matter integrity in antipsychotic-naïve first-episode psychosis patients assessed by a DTI principal component analysis

Abstract: Introduction Diffusion tensor imaging (DTI) studies in patients with schizophrenia have shown abnormalities in the microstructure of white matter tracts. Specifically, reduced fractional anisotropy (FA) has been described across multiple white matter tracts, in studies that have mainly included patients treated with antipsychotic medications. Objective To compare FA in antipsychotic-naïve patients experiencing a first episode of psychosis (FEP) to FA in healthy controls to demonstrate that the variance of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 61 publications
5
13
0
Order By: Relevance
“…Our finding is consistent with studies showing reduced FA (Alvarado-Alanis et al, 2015; Cheung et al, 2008) or elevated RD (Lee et al, 2013) in the midbrain of first-episode patients. This is important because the substantia nigra and ventral tegmental area are the primary sites of dopamine synthesis, and patients have elevated dopamine release in the striatum (Abi-Dargham et al, 1998; Laruelle et al, 1996), one of the targets of midbrain dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding is consistent with studies showing reduced FA (Alvarado-Alanis et al, 2015; Cheung et al, 2008) or elevated RD (Lee et al, 2013) in the midbrain of first-episode patients. This is important because the substantia nigra and ventral tegmental area are the primary sites of dopamine synthesis, and patients have elevated dopamine release in the striatum (Abi-Dargham et al, 1998; Laruelle et al, 1996), one of the targets of midbrain dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 93%
“…DTI measurements could potentially be influenced by antipsychotic medication (Minami et al, 2003). However, we note that DTI abnormalities have been observed in medication-naïve patients (Alvarado-Alanis et al, 2015; Cheung et al, 2008; Cheung et al, 2011; Gasparotti et al, 2009; Mandl et al, 2013). Second, although our goal was to explore the relationship between the neuronal biochemistry of two cortical regions and the white matter tract connecting them, the MRS voxels included both gray and white matter, which both contribute to the NAA and Glx signals and have different concentrations (Sailasuta et al, 2008; Wang and Li, 1998).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 136 White matter pathology in schizophrenic patients and in PolyI:C mice has also been shown in vivo using diffusion tensor imaging, which is a particular kind of magnetic resonance imaging often used to analyze white matter structural integrity. 137 Using this method, Alvarado-Alanis et al 138 and Li et al 139 found white matter abnormalities in frontostriatal–limbic tracts in the adult PolyI:C mice, reflecting the human abnormalities especially in treatment-naive first-episode patients.…”
Section: Maternal Immune Activation Modelsmentioning
confidence: 99%
“…This dysconnection hypothesis suggests that schizophrenia may be understood in terms of cognition and pathophysiology as aberrant brain integration (Friston, 1998). It has been suggested that abnormalities in white matter microstructure may produce the anatomical substrate for the dysconnectivity hypothesis (Alvarado-Alanis et al, 2015;Weinberger, 1987). White matter deficits are the most consistent neuroimaging findings in this disorder and it has been reported that white matter integrity may be predictive of conversion to schizophrenia and functional outcome (reviewed in Karlsgodt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%